The British navy in the Caribbean - Grainger, John D. (Boydell Press, 2021)
A survey of the activities of the British navy in the Caribbean from the voyages of sixteenth century English adventurers such as John Hawkins and Francis Drake through the great wars of the seventeenth and eighteenth centuries against the Dutch, Spanish and French and Britain's declining role thereafter.